Diversity of Nitrile Hydratase and Amidase Enzyme Genes in Rhodococcus erythropolis Recovered from Geographically Distinct Habitats - Brandão, Pedro F. B. (American Society for Microbiology, 2003)
A molecular screening approach was developed in order to amplify the genomic region that codes for the α- and β-subunits of the nitrile hydratase (NHase) enzyme in rhodococci. Specific PCR primers were designed for the NHase genes from a collection of nitrile-degrading actinomycetes, but amplification was successful only with strains identified as Rhodococcus erythropolis. A hydratase PCR product was also obtained from R. erythropolis DSM 43066(T), which did not grow on nitriles. Southern hybridization of other members of the nitrile-degrading bacterial collection resulted in no positive signals other than those for the R. erythropolis strains used as positive controls. PCR-restriction fragment length polymorphism-single-strand conformational polymorphism (PRS) analysis of the hydratases in the R. erythropolis strains revealed unique patterns that mostly correlated with distinct geographical sites of origin. Representative NHases were sequenced, and they exhibited more than 92.4% similarity to previously described NHases. The phylogenetic analysis and deduced amino acid sequences suggested that the novel R. erythropolis enzymes belonged to the iron-type NHase family. Some different residues in the translated sequences were located near the residues involved in the stabilization of the NHase active site, suggesting that the substitutions could be responsible for the different enzyme activities and substrate specificities observed previously in this group of actinomycetes. A similar molecular screening analysis of the amidase gene was performed, and a correlation between the PRS patterns and the geographical origins identical to the correlation found for the NHase gene was obtained, suggesting that there was coevolution of the two enzymes in R. erythropolis. Our findings indicate that the NHase and amidase genes present in geographically distinct R. erythropolis strains are not globally mixed.